HOW YOUTUBE INFLUENCES CHILDREN LANGUAGE ACQUISITIONS AND IMPACT THEIR ADVANCEMENT?: AN INVESTIGATION TO THE ELEMENTARY SCHOOL’S KIDS - Ilfan Askul Pehala; Mirdad Mirdad; Dian Masri; Andi Ati Mappalettu; Syamsul Amar Al-Atif (Haluan Sastra Budaya, 2023)
This study aims to investigate the children language acquisition advancement based on YouTube platform influence. To achieve this aim, this research applied qualitative methods as qualitative research. The participants of this study were three children at the elementary level and their parents in a different place. The data of this study were attained from interviews using open-ended questions and observations. Thematic analysis was implemented in this study. The result of the analysis showed that YouTube has positively influenced the children’s language acqusition development. The duration of watching is directly proportional to the level of children language acquisition development. The variations in children’s vocabulary are influenced by the type of content. Video blogging is part of informal environment for children in learning new things as also language given the benefit in this research which is hoped to lead more research in the language acquisition development in children level.